Abnormal bone remodelling and increased levels of macrophage inflammatory protein-1 alpha (MIP-1α) in Waldenström macroglobulinaemia - Terpos, E.; Anagnostopoulos, A.; Kastritis, E.; Bamias, A.; Tsionos, K.; Dimopoulos, M.-A. (British Journal of Haematology, 2006)
Serum levels of macrophage inflammatory protein-1 alpha (MIP-1α) and bone remodelling markers were evaluated in 38 patients with Waldenström macroglobulinaemia (WM) and correlated with clinical and laboratory variables. MIP-1α was elevated in WM; untreated patients had higher MIP-1α levels than patients in remission or with active disease after treatment. MIP-1α correlated with increased bone resorption, β2- microglobulin and splenomegaly. Receptor activator of nuclear factor-κB ligand serum levels were elevated in WM patients; the subsequent increased bone resorption was balanced by a comparable elevation of osteoprotegerin production and bone formation. These findings may explain the absence of lytic lesions in WM patients and suggest a potential role of MIP-1α in WM. © 2006 Blackwell Publishing Ltd.
Keywords: bone markers; Macrophage inflammatory protein-1 alpha; Osteoprotegerin; Receptor activator of nuclear factor-κB ligand; Waldenström macroglobulinaemia